2018
DOI: 10.21608/ijaf.2018.95501
|View full text |Cite
|
Sign up to set email alerts
|

A Gap Analysis of the Essential Competencies Expected and Perceived from Hospitality Graduates in the Industry: The Case of Egypt

Abstract: The purpose of this study is to examine, identify the essential competencies expected and perceived from hospitality graduates in the industry. A gap means analysis technique used to analyze hospitality managers' expectations and perceptions about Employment of Graduates in the hospitality industry. Industry management conceded that hospitality education modules need to reflect recent and future industry challenges and improvements to guarantee graduates are outfitted with suitable and industry-relevant compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Unfortunately, it was noticed that over 30% of the total hospitality workforce does not possess the basic capabilities and skills needed for the industry (Hossny 2018). Scholars have shown that hotel operators are suffering from a lack of graduates' soft skills (Dhaliwal and Misra 2020) because many hospitality institutions don't implant the required skills in the curriculum, which results in an unskilled and unemployable workforce (Dhaliwal and Misra 2020).…”
Section: Curriculum and Graduate's Employabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…Unfortunately, it was noticed that over 30% of the total hospitality workforce does not possess the basic capabilities and skills needed for the industry (Hossny 2018). Scholars have shown that hotel operators are suffering from a lack of graduates' soft skills (Dhaliwal and Misra 2020) because many hospitality institutions don't implant the required skills in the curriculum, which results in an unskilled and unemployable workforce (Dhaliwal and Misra 2020).…”
Section: Curriculum and Graduate's Employabilitymentioning
confidence: 99%
“…Concerning the hospitality industry, hotel management graduates experience a shortage of the necessary skills, which makes them less relevant to the industry, and thus less attractive for hotel recruitment (Hossny 2018), which affects the graduates' employability and leads to an increase in unemployment and underemployment among higher education graduates (Brewer 2013, Ejiwale 2014, Ramisetty and Desai 2017, Crespin et al 2019.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations